Pollution characteristics and health risk assessment of potentially toxic elements in soils around China’s gold mines: a meta-analysis - Chen, Li; Wang, Jingzhe; Guo, Xuetao; Wu, Hao; He, Haoran; Fang, Linchuan (Environmental geochemistry and health, 2022)
Since toxic element pollution is widespread in soils near gold mines due to increasing mining activities, the adverse effects of potentially toxic elements (PTEs) in the soils on ecological systems and human health cannot be ignored. However, assessments of PTE pollution in soils and their ecological-health risks on a national scale are still limited. Here, the concentrations of eight PTEs in soils near gold mines throughout China were obtained from published articles. Based on these data, the pollution levels and ecological-health risks of the eight PTEs in soils were comprehensively estimated. The results showed that the average contents of As, Cr, Cd, Pb, Hg, Cu, Ni, and Zn were 81.62, 79.82, 1.04, 206.03, 2.05, 40.82, 71.82, and 130.42 mg kg −1 , respectively, which exceeded the corresponding background values for soils. Most of the examined soils were heavily polluted by Hg and Cd, and higher pollution levels were found in the Henan and Shaanxi Provinces than in other regions. The average potential ecological risk value of all PTEs was 2534.71, indicating the presence of very high risks. Contribution of Hg to the potential ecological risk was more than 80%. For adults, all hazard index (HI) values of noncarcinogenic risks were below the safe level of 1.00. For children, none of the HI values exceeded the safe level, with the exception of As (HI = 1.81); nevertheless, four PTEs (As, Cr, Cu, and Ni) presented unacceptable carcinogenic risks. This study provides scientific basis for controlling PTE contamination and reducing the health risks in soils near gold mines worldwide. Graphical Abstract